Towards an Understanding of Greek Politics - Spourdalakis, Michalis (Études helléniques / Hellenic Studies, 1984)
This article outlines developments in the Greek social formation over the past 30 yars. The argument it tries to put forward is that today’s political configuration in Greece is not simply the natural evolution of the last few decades. Rather, Greek politics today, regardless of their orientation, are struggling to come to terms with contradictions which first appeared in the early 1960’s. The Greek economy presents a schizophrenic and uneven development along the lines of a partnership with -and not a mere dependency on- imperialism (through shipping, financial and commercial capital). It is this economic situation along with the social and political contradictions which it generated that confront not only the present-day governmental policies, but those opposed to them as well. In addition, an attempt is made to locate the origins of today’s political configuration. More concretely, to locate the articulation of “socialism” by the PA.SO.K. in the political events of the mid -60’s and the resistance “movement” during the dark days of the junta.